PERLINDUNGAN HAK ASASI MANUSIA BAGI NARAPIDANA DISABILITAS DI LEMBAGA PEMASYARAKATAN - Setyowati, Tri Sulis; Subroto, Mitro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This article discusses the challenges faced by prisoners with disabilities within correctional institutions concerning the protection of their human rights. Prisoners with disabilities are often vulnerable to violations of their basic rights, such as the right to humane treatment, privacy, and access to adequate healthcare. In this context, this article also reviews policies and best practices that can be implemented to ensure the protection of the rights of prisoners with disabilities. Several successful case studies in ensuring the human rights of prisoners with disabilities will also be presented. Through an in-depth understanding of the issue, this article aims to raise awareness about the importance of human rights protection for prisoners with disabilities in correctional institutions. Keywords: Prisoners; Disability; Correctional Institutions; Human Rights